Innovative Design of Tumor Registry Database Program for Musculoskeletal Oncology Service - Charoenlap, MD, Chris; Hongsaprabhas, MD, Chindanai (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To demonstrate an innovative program design which combines tumor registration and electronic health records that suit Thai orthopedic oncologist practice. Methods: The Thai Musculoskeletal Tumor Society (TMTS) database program is a Microsoft Access database created for bone and soft tissue tumor services. Only significant parameters are recorded and all data forms are based on user-friendly concepts. Apart from exporting data to a web-based tumor registration, all input data will be utilized to facilitate complex oncology work such as printing out patient records or patient transfer forms, showing disease demographic data, retrieving particular case series, and post-operative time calculations with management planning. Results: The TMTS database program was designed for new emerging orthopedic oncology units with limited resources to possess a standard tumor database for clinical use and to promote research collaboration between small and large tumor centers. Conclusion: By adopting the specialty-specific TMTS database, we expected increases both in efficiency of tumor patient care and collaborative multi-institutional research.